PENGARUH ENTREPRENEURIAL ORIENTATION TERHADAP KINERJA EKSPORTIR : STUDI PADA UMKM DI TANGERANG - Wulandari, Respati (Jurnal Ekonomi : Journal of Economic, 2017)
UMKM play an important role in the economy of the State. In Indonesia, especially the number of UMKM business actors are among the most among other countries, especially since 2014. Currently the government is very supportive of the development of UMKM. One of the development of umkm is to improve its performance. The hope UMKM not only can succeed in Indonesia alone, but can continue to improve the performance of his company by doing export. Forms of support made by the government in increasing exports such as increased access and expansion of export markets for UMKM products. UMKM export increase continues to be increased by the government in every region, where one of its territory is Tangerang. The large and growing number of UMKM in Tangerang area has made UMKM in Tangerang continue to get a lot of government attention. This study will analyze whether the key success of exporters in tangerang region, whether exporters who have souls oriented entrepreneurship is more successful in running its business. This study will analyze what factors are needed by a successful exporter, whether risk-taking, proactive, innovative, or aggressive. By knowing it, it is hoped the government can further improve the spirit of the entrepreneur, so this research will contribute in improving the performance of UMKM, especially to export.Keywords: entrepreneurial, exporter, umkm, indonesia, performance